Combating Impermissible Tax Avoidance through Efficient Administrative Approaches: What SARS can Learn from its Canadian Counterpart - Steenkamp, Lee-Ann (Comparative and International Law Journal of Southern Africa, 2022)
Impermissible tax avoidance transactions cross the dividing line between legal tax avoidance and illegal tax evasion. In response, governments across the globe have adopted legislative, judicial and administrative measures to combat this type of tax avoidance. This article reviews the use of the administrative techniques employed by the Canada Revenue Agency (CRA). These include awareness resources, monitoring tools, audits and administrative penalties. Through the evaluation of Canada’s regime, the article seeks to make recommendations in an attempt to improve the South African administrative approach. It is proposed that the South African Revenue Service (SARS) continues to develop a cogent compliance programme in order to improve tax compliance.